Panel analysis of FDI in fast emerging ASEAN countries / Catherine S F Ho and Ahmad Husni Mohd Rashid - Ho, Catherine S F; Mohd Rashid, Ahmad Husni (2013)
This paper investigates significant determinants of foreign direct investment (FDI) in five ASEAN countries namely Indonesia, Malaysia, the Philippines, Singapore and Thailand from 1975 to 2009. It applies both individual and panel data analyses on these fast emerging countries and findings depict that the rate of economic growth and degree of openness significantly affect FDI flows in the majority of these countries. The Malaysian exchange rate directly affects FDI flows into the country while manufacturing output attracts FDI into the Philippines. Inflation rate plays a significant role on FDI flows for Thailand. The model for country specific factors indicates that different factors are more important for counties in differing stages of development. For the panel of ASEAN countries, consumer income and employment emerged as significant drivers of foreign investments. In Indonesia and the Philippines employment negatively affects investments, while tourism positively affects FDI in the Philippines and Malaysia. Other significant factors include the level of consumer income, skill and knowledge, and infrastructure development. Results from this study should provide policy makers with the latest information to attract FDI.